Analysis of Factors Affecting Antiretroviral Adherence in HIV/AIDS Patients - Mochamad Makin; Irfansyah Baharuddin Pakki; Akhmad Azmiardi; Ratno Adrianto; Yadi Yadi; Ida Ayu Indira Dwika Lestari (GLOBAL HEALTH SCIENCE GROUP, 2025)
Human Immunodeficiency Virus (HIV) remains a major global public health issue, with antiretroviral (ARV) therapy playing a critical role in its management. Adherence to ARV therapy is essential to suppress viral load, prevent drug resistance, and improve the quality of life of people living with HIV/AIDS (PLWHA). However, cases of non-adherence persist. At RSUD A. Wahab Sjahranie, a referral hospital in East Kalimantan, 16% of patients have been found to be non-adherent to their ARV medication. Ensuring adherence is vital to avoid complications and prevent HIV transmission. This study aims to identify and analyze the factors influencing ARV adherence among HIV/AIDS patients at the Anyelir Outpatient Clinic, RSUD A.W. Sjahranie, Samarinda. This study employed a quantitative analytical approach with a cross-sectional design. It involved 106 HIV/AIDS patients who were actively receiving antiretroviral therapy (ART). The independent variables included knowledge, self-efficacy, duration of therapy, side effects, family support, social support, and healthcare staff attitude. Data were collected using a structured questionnaire administered directly to respondents and supported by secondary data from medical records. A total sampling technique was applied, and data were analyzed using chi-square tests and logistic regression at a 95% significance level. A total of 85.8% of respondents were classified as adherent to ARV treatment. Bivariate analysis showed that knowledge (p = 0.019), family support (p = 0.018), social support (p = 0.011), healthcare staff attitude (p = 0.006), and self-efficacy (p = 0.002) were significantly associated with ARV adherence. Multivariate analysis identified family support (OR = 4.275), healthcare staff attitude (OR = 6.834), and self-efficacy (OR = 20.241) as the most influential factors. Knowledge, side effects, family support, social support, healthcare staff attitude, and self-efficacy are significant determinants of ARV adherence among PLWHA. Among these, self-efficacy emerged as the most dominant factor.